IMPLEMENTASI MEDIA GAMBAR DALAM PENGUASAAN KOSAKATA BAHASA ARAB UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Habibillah, Erik; Eni Fariyatul Fahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The goal is to learn how students can understand Arabic language learning vocabulary mastery through image media in improving learning outcomes. administrators can help improve teacher skills through formal and informal means. The motivation behind this research is 1. to describe the ability of grade 3 students in mastering Arabic learning vocabulary using image media at SD Muhammadiyah 2 Surabaya; 2. to explain image media in mastering Arabic learning vocabulary in improving the learning outcomes of grade 3 students SD Muhammadiyah 2 Surabaya; 3. to describe the elements that inhibit the use of image media in mastering Arabic language learning vocabulary for grade 3 students at SD Muhammadiyah 2 Surabaya: 4. to improve the learning outcomes of grade 3 students by using image media in mastering Arabic language learning vocabulary at SD Muhammadiyah 2 Surabaya. This research was carried out at SD Muhammadiyah 2 Surabaya, with the objects being educators and students. This research uses qualitative research methods, using information collection procedures through observation, interviews and documentation.